E tudo o podcast levou: uma reflexão sobre a programação radiofónica e a produção de podcasts pelas principais rádios portuguesas - Morais, Ricardo (2022)
In this chapter, we seek to reflect on the production of podcasts by the main Portuguese radio stations. Data collected in recent years points to an increase in the consumption and production of podcasts. In many studies, the rise of consumption has been related to a decrease in radio listening. Thus, observing the growth in the consumption of podcasts, we sought to understand whether radios have been investing in this field as a strategy to diversify content and reach new listeners. To carry out this analysis, we considered the section dedicated to podcasts on the radio's websites. Through a content analysis, we verified that there is, above all, a tendency to reproduce programs in the form of podcasts. Data collected allow us to question the relationship between radio programming and the production of podcasts, while highlighting the importance of deepening the analysis of consumption habits in the Portuguese radio ecosystem.